Framing Immigration News in Spanish Regional Press. (7th September 2010) - Cheng, Lifen; Igartua, Juan José; Palacios, Elena; Acosta, Tania; Palito, Socorro
Abstract: In this paper, an exploratory content analysis has been developed for a case study on the topic of immigration reported in the regional newspapers of the largest Spanish autonomous community, Castilla and Leon. This study based its research conceptualization on the framing theory in mass communication. In addition to usual issue frames and issue images, two framing devices were established for analytic variables ‐‐ the index of importance and the index of affective attribute. They formed a frame package capable of making latent frames evident by their linkage to manifest frames. Comparing to the general assumption of relevant‐bad‐news production, results obtained in this study proved that, on occasion, negative news stories could be reported as less relevant than the positive ones. The outcomes also show how concept mapping of frames was applicable to immigration issues and immigrants' visual aspects of immigrant communities that were systematically articulated and disseminated by the press in this regional society of Spain.